PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. GALESONG MANDIRI MAKASSAR - Samsul Rizal; Ismail Rasulong; Nirmala Sari (JEMMA (Journal of Economic, Management and Accounting), 2024)
This research aims to examine the influence of organizational culture and job satisfaction on employee performance at PT. Sinar Galesong Mandiri Makassar. The research design used in this research uses a questionnaire method, where this research takes samples from one population and uses a questionnaire as a data collection tool. The population in this research is 150 employees of PT. Sinar Galesong Mandiri Makassar. The sampling technique used the Slovin formula with a sample size of 60 respondents. The data analysis technique used was multiple linear regression analysis using Statistical Product and Service Solution (SPSS). The research results partially show that the variables of organizational culture and job satisfaction each have a significant influence on employee performance